Argentina : Can Performance Payments Improve Newborn Health? - World Bank (Washington, DC, 2015)
Poor children face barriers to healthy development even before they are born. Their mothers may not have nutritious food or proper prenatal care, which can harm a baby s brain development when it needs it most. Mothers may not deliver in a health facility nor have a skilled birth attendant present, increasing the risk of complications and ultimately putting their life and that of the baby at risk. In Argentina, the World Bank supported a government program, Plan Nacer, to improve maternal-child health outcomes through increased coverage and quality of health services. The program gives provincial authorities financial incentives for enrolling pregnant women and children in the program and for achieving specific primary health care goals. An impact evaluation found that Plan Nacer improved the birth weight of babies and reduced newborn deaths, while improving access to public health facilities and boosting the quality of care. The evidence from this evaluation will equip policy makers in low and middle income countries with additional information when designing health programs aimed at improving specific outcomes. As governments around the world look for ways to create effective programs to help their poorest citizens, the results from this impact evaluation provide an example of how health sector reforms can give children the right start in life.